Credibility of green advertising: six elements that drive credibility in green advertising - Verleye, Gino; De Ruyck, Arjan; Vermeulen, Wim; Schoenaers, Inez (Frontiers in Communication, 2023)
The goal of this academic research was to examine to what extent sustainable advertising messages are perceived as credible by the Belgian consumer. We wanted to investigate how credibility arises in sustainable commercials and what the impact of credible green advertising can be. We started with a literature study to uncover possible determinants of credibility and were able to distinguish six elements that drive credibility in green advertising. These six elements are honesty, clearness, details, commitment, urgency, and shared value. In order to validate the elements with significant evidence and examine their impact on green motivation and brand consideration, we ran a survey in which our individual respondents saw 5 sustainable commercials. These were randomly selected from a collection of 95 commercials that had been broadcasted in Belgium in the last 24 months before August 2021. 600 respondents participated in this survey, representative for Belgian consumers aged 19 to 90 years old. The results make clear that credibility is lacking and the key to effectiveness on many levels. Our six elements explain 72% of credibility in green advertising. Credibility and its six elements explain 59% of consumers’ motivation to prefer sustainable products over conventional products. Together they explain 28% of brand consideration of the advertised sustainable product. Future success of sustainability may depend on whether brands can initiate switching the mindset of consumers with green advertising. This requires that green advertising is honest, shows commitment and urgency, provides details and clearness, and focuses on shared value for companies and consumers.